Knights at Court : Courtliness, Chivalry, and Courtesy from Ottonian Germany to the Italian Renaissance. - Scaglione, Aldo. (Berkeley : University of California Press, 2022)
Knights at Court is a grand tour and survey of manners, manhood, and court life in the Middle Ages, like no other in print. Composed on an epic canvas, this authoritative work traces the development of court culture and its various manifestations from the latter years of the Holy Roman Empire (ca. A.D. 1000) to the Italian Renaissance of the fifteenth and sixteenth centuries. Leading medievalist and Renaissance scholar Aldo Sc.
Print version record.
JSTOR
Keywords: Courts and courtiers; Civilization, Medieval; Courts and courtiers in literature; Chivalry; Knights and knighthood; Literature, Medieval -- History and criticism; Humanism; Cours et courtisans; Civilisation médiévale.; Cours et courtisans dans la littérature.; Chevalerie; Littérature médiévale -- Histoire et critique; Humanisme; humanism; Chivalry; Civilization, Medieval; Courts and courtiers; Courts and courtiers in literature; Humanism; Knights and knighthood; Literature, Medieval; Criticism, interpretation, etc